Pengaruh kenaikan harga dan kualitas kedelai terhadap keputusan pembelian kedelai di masa pandemi Covid-19 - Andri Yansah; Nisa' Ulul Mafra; Erfan Robyardi (Jurnal Kajian Manajemen dan Wirausaha, 2021)
This study aims to determine (1) the effect of price increases on purchasing decisions, (2) the effect of soybean quality on purchasing decisions, (3) the effect of price increases and soybean quality on soybean purchasing decisions during the COVID-19 pandemic at the morning market in Gunung Batu Village. Sampling using saturated samples. Research data obtained by distributing questionnaires about price increases, soybean quality and purchasing decisions to 30 respondents who are tofu-tempe traders. Data analysis techniques used in this study are multiple linear regression analysis, coefficient of determination test, correlation coefficient test and hypothesis testing. The results of this study, namely the t test, the results showed that the variable price increase and soybean quality partially had a significant influence on soybean purchasing decisions during the Covid-19 pandemic at the morning market in Gunung Batu Village, the F test obtained results, namely the variable price increase and soybean quality. Simultaneously there was a significant influence on soybean purchasing decisions during the Covid-19 pandemi at the Gunung Batu Village morning market.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//